2020
DOI: 10.1002/er.5402
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of a direct evaporative cooling approach for Li‐ion battery thermal management

Abstract: Summary A desirable operating temperature range and small temperature gradient is beneficial to the safety and longevity of lithium‐ion (Li‐ion) batteries, and battery thermal management systems (BTMSs) play a critical role in achieving the temperature control. Having the advantages of direct access and low viscosity, air is widely used as a cooling medium in BTMSs. In this paper, an air‐based BTMS is modified by integrating a direct evaporative cooling (DEC) system, which helps reduce the inlet air temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 35 publications
(39 reference statements)
0
15
0
Order By: Relevance
“…As one of advanced thermal management systems, direct cooling system takes the advantages of liquid-cooling system and PCM, while the disadvantages are limited by using innovative designs. 19,41 The liquid PCM is adopted to achieve two-stage cooling for enhancing the efficiency, while less necessary components limit the demand of extra mass or space. The liquid coolant flows in the cooling plate connected with battery pack, and the coolant will exchange heat with plate and batteries by conduction and convection.…”
Section: Overview Of Direct Cooling Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…As one of advanced thermal management systems, direct cooling system takes the advantages of liquid-cooling system and PCM, while the disadvantages are limited by using innovative designs. 19,41 The liquid PCM is adopted to achieve two-stage cooling for enhancing the efficiency, while less necessary components limit the demand of extra mass or space. The liquid coolant flows in the cooling plate connected with battery pack, and the coolant will exchange heat with plate and batteries by conduction and convection.…”
Section: Overview Of Direct Cooling Systemmentioning
confidence: 99%
“…The operational mechanism of direct cooling system is that the refrigerating coolant will directly cool the battery system based on evaporating phase‐change process. As one of advanced thermal management systems, direct cooling system takes the advantages of liquid‐cooling system and PCM, while the disadvantages are limited by using innovative designs 19,41 . The liquid PCM is adopted to achieve two‐stage cooling for enhancing the efficiency, while less necessary components limit the demand of extra mass or space.…”
Section: Classification Of Thermal Management Systemmentioning
confidence: 99%
“…Many studies have reported on air and liquid battery cooling as cooling media 14‐20 . Zhao et al 21 presented modified air‐based BTMS by integrating a direct evaporative cooling (DEC) system, which helps reduce the inlet air temperature for enhanced heat dissipation. Yang et al 22 studied Z‐type flow parallel liquid cooling battery pack with different flow paths.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of thermal management strategies have been proposed in recent years. According to the heat transfer medium used, the BTMS can be mainly divided into air cooling, 4‐6 liquid cooling, 7‐9 and phase change material (PCM) cooling 10‐12 . The advantages of air cooling system are low cost and simple structure, 13 but its heat dissipation effect is limited; it is difficult to guarantee the power battery with high capacity to operate at the optimal temperature under high loads or in hot conditions.…”
Section: Introductionmentioning
confidence: 99%